The efficacy and safety of mirabegron and α-adrenergic receptor antagonist in the treatment of distal ureteral stones: a systematic review and meta-analysis - Guo, Yicheng; Sun, Fengze; Wang, Yini; Li, Yanfei; Wang, Tianqi; Ma, Xiaohong; Wu, Jitao (Frontiers in Pharmacology, 2025)
IntroductionTo systematically evaluate the efficacy and safety of mirabegron compared to α-adrenergic receptor antagonists for treating distal ureteral stones.MethodsA comprehensive search of EMBASE, PubMed, and Cochrane databases was conducted to identify studies comparing mirabegron and α-adrenergic receptor antagonists for stone expulsion. The primary outcome was stone expulsion rate (SER), and secondary outcomes included stone expulsion interval (SEI) and pain episode frequency. Risk ratio (RR) and mean differences (MD) with 95% CIs were calculated.ResultsSix studies involving 487 participants were included. There was no significant difference in SER between mirabegron and α-adrenergic receptor antagonists (RR = 1.06; 95% CI = 0.93–1.22; P = 0.34). SEI showed no significant difference either (MD = 0.05; 95% CI = −3.23 to 3.34; P = 0.58). However, pain episodes were significantly reduced in the mirabegron group (MD = −0.36; 95% CI = −0.63 to −0.09; P = 0.01). Subgroup analysis showed reduced pain episodes with mirabegron versus silodosin but not tamsulosin. Mirabegron also had fewer side effects like headache (RR = 0.34; 95% CI = 0.13–0.87; P = 0.02) and orthostatic hypotension (RR = 0.11; 95% CI = 0.02–0.55; P = 0.008), while dizziness and ejaculation dysfunction rates were comparable.ConclusionMirabegron reduced pain episodes during treatment for distal ureteral stones, particularly when compared to silodosin, despite no significant differences in SER or SEI. Its favorable safety profile suggests potential as a therapeutic option. Further randomized controlled trials are needed to confirm these findings.